Risk factors for miliary tuberculosis in children - Clarissa Cita Magdalena; Budi Utomo; Retno Asih Setyoningrum (Paediatrica Indonesiana, 2017)
Background Miliary tuberculosis (TB) is a fatal form of tuberculosis with severe clinical symptoms and complications. The mortality rate from this disease remains high, therefore, it is important to identify the risk factors for miliary TB for early detection and treatment.Objective To identify risk factors for miliary tuberculosis in children.Methods A case-control study of children aged 0-14 years with miliary TB was conducted in Dr. Soetomo Hospital from 2010 to 2015. Data were taken from medical records. Case subjects were children with miliary TB, and control subjects were children with pulmonary TB . Patients with incomplete medical records were excluded. Case subjects were identified from the total patient population; control subjects were included by purposive sampling, with case:control ratio of 1:1. Potential risk factors were age, nutritional status, BCG immunization status, and history of contact with TB patients. Statistical analyses were done with Chi-square and logistic regression tests. P values < 0.05 were considered to be statistically significant.Results A total of 72 children were analyzed, with 36 case and 36 control subjects. Nutritional status had a significant associatation with miliary TB in children (OR 3.182; 95%CI 1.206 to 8.398; P=0.018) in both bivariate and multivariate analyses. The probability of a child with moderate or severe undernutrition developing miliary TB was 76.09%. Other factors were not significantly associated with miliary TB.Conclusion Nutritional status is significantly associated with miliary TB in children, and moderate or severe undernutrition increases the risk for developing miliary TB.